Analysis of spatial distribution and inventory of radioactivity within the uranium mill tailings impoundment - D. O. Bugai; G. V. Laptev; O. S. Skalskyy; T. V. Lavrova; R. Avila (Âderna Fìzika ta Energetika, 2015)
Results are presented of the characterization of radioactivity inventory of Zapadnoe uranium mill tailings impoundment situated at Pridneprovsky Chemical Plant (PChP; Dneprodzerzhinsk, Ukraine). Analyses of radioactivity data set based on analytical studies of core material from 15 characterization boreholes allowed significantly refining waste volume and radioactivity inventory estimates. Geostatistical analyses using variogram function have established that radioactivity distribution in Zapadnoe tailings is characterized by regular spatial correlation patterns. Ordinary kriging method was applied to assess distribution of radioactivity in 3D. Results of statistical analyses suggest significant redistribution of uranium in the dissolved form in the residues (presumably due to water infiltration process). The developed structural model for radioactivity distribution is used for further risk assessment analyses. Derived radioactivity correlation scales can be used for optimization of sample collection when characterizing the PChP Site and similar contaminated sites elsewhere.